Comparing socially disadvantaged smokers who agree and decline to participate in a randomised smoking cessation trial. Issue 9 (14th September 2015) - Bonevski, Billie; Twyman, Laura; Paul, Chris; D'Este, Catherine; West, Robert; Siahpush, Mohammad; Oldmeadow, Christopher; Palazzi, Kerrin; Bryant, Jamie; Guillaumier, Ashleigh
Abstract : Objectives: This study examined sociodemographic, smoking and psychosocial characteristics associated with consent to participate in a smoking cessation trial for socially disadvantaged smokers. Design: Baseline data were collected prior to seeking consent for the Call it Quits, a randomised controlled trial. Setting: An Australian social and community service organisation. Sociodemographic, smoking and psychosocial characteristics were compared between smokers who agreed or declined to participate. Participants: Of the 584 smokers invited to participate, 431 (74%) consented and 153 (26%) declined. Results: Logistic regression modelling indicates the ORs of participation were twice as high for those reporting 'high' motivation to quit compared to the 'moderate' motivation group, and five times higher than the 'low' motivation group (p=0.007). The ORs of consenting were higher for those with a preference for gradual reduction in cigarettes in quit attempts compared with 'no preference'. The ORs were lower for those reporting 'don't know' regarding their enjoyment of smoking compared to 'not at all' enjoying smoking, and reporting that fewer of their family or friends smoked compared to 'most or all'. Conclusions: This study is the first to examine the characteristics of socially disadvantaged smokers who consent or decline to participate in a smoking cessation trial. Low-income smokers who are motivated to quit, are not enjoying smoking, had family or friends who smoked, and who are interested in gradual cessation approaches may be more likely to participate in a smoking cessation trial. Trial registration number: ISRCTN85202510.